2006
DOI: 10.1080/10428190500395472
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin lymphoma with high adenosine deaminase levels mimicking peritoneal tuberculosis: An unusual presentation

Abstract: Abdominal tuberculosis is still a medical problem in developing countries. The clinical presentation of tuberculous (TB) peritonitis may be similar to that of peritoneal carcinomatosis. Therefore, its diagnosis is rather difficult only with laboratory investigations. Ascitic fluid adenosine deaminase (ADA) activity has been proposed as a useful diagnostic test in tuberculous peritonitis, as many studies reported high ADA levels in TB peritonitis. On the other hand, ADA activity is usually lower in peritoneal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…In clinical practice, it is frequently considered as a noninvasive diagnostic test for tuberculosis with 90-100% sensitivity and 89-100% specificity [3]. Additionally, it has been shown in several studies that ADA activities may be useful both in diagnosis and monitoring of some malignancies [4][5][6]. Most of these studies are based on purine enzymatic differences between benign and cancer tissues.…”
Section: Introductionmentioning
confidence: 98%
“…In clinical practice, it is frequently considered as a noninvasive diagnostic test for tuberculosis with 90-100% sensitivity and 89-100% specificity [3]. Additionally, it has been shown in several studies that ADA activities may be useful both in diagnosis and monitoring of some malignancies [4][5][6]. Most of these studies are based on purine enzymatic differences between benign and cancer tissues.…”
Section: Introductionmentioning
confidence: 98%
“…Especially diagnosis of exudative ascites (including lymphoma, various for ms of peritonitis, peritoneal carcinomatosis, and peritoneal tuberculosis) is a dilemma. Non-invasive tests such as laboratory tests, acid-fast stain and culture of the ascitic fluid, ADA levels are usually insufficient for the differential diagnosis of ascites [19,20] . Therefore laparoscopy with directed biopsy is necessary for the diagnosis of ascites.…”
Section: Introductionmentioning
confidence: 99%
“…The increased ADA was commonly found in the tuberculous pleural fluid. Nevertheless, an elevated ADA activity in pleural fluid has also been reported in some cases of benign or malignant diseases, such non-Hodgkin’s lymphoma, breast cancer [7,8]. Yokoyama et al also reported a myelomatous pleural effusion case with high ADA activity in pleural effusion [9], but the ADA activity in our patient was much higher.…”
Section: Discussionmentioning
confidence: 39%